Three‐Dimensional Crustal Structures of the Shanxi Rift Constructed by Rayleigh Wave Dispersion Curves and Ellipticity: Implication for Sedimentation, Intraplate Volcanism, and Seismicity. Issue 11 (13th November 2020) - Xu, Hongrui; Luo, Yinhe; Yang, Yingjie; Shen, Weisen; Yin, Xiaofei; Chen, Guoxiong; Yang, Xiaozhou; Sun, Shida
Abstract: The Shanxi Rift is one of the world's largest Cenozoic continental rifts. It is one of the most earthquake prone areas in China and has volcanic activities characterized by small volumes of magma. In order to study continental rifting mechanism, intraplate volcanism, and seismicity of the Shanxi Rift, we construct a high‐resolution 3‐D lithospheric shear velocity (Vs) model with a focus of the crust by jointly inverting Rayleigh wave dispersion curves and ellipticity measurements. Compared with published models, our 3‐D Vs model has improved the resolution for shallow structures. Our model reveals several significant velocity features. (1) The sedimentary layer of the Datong Basin is much thicker than those in the southern Shanxi Rift, implying that the sedimentation rate of the Datong Basin is higher, which could be attributed in part to asthenosphere upwelling beneath the Datong Basin area in the past few Ma in addition to passive rifting. (2) A low‐velocity body is observed in the middle crust beneath the Datong Volcanoes, suggesting the presence of a small amount of partial melting in the middle crust. (3) Lower velocities in the middle and lower crust beneath the Datong Basin are coincident with the shallowing of deep earthquakes from the southern to northern Shanxi Rift in the crust, suggesting that higher temperature may elevate the brittle‐to‐ductile transition zone, leading to the shallowing of focal depths of earthquakes in the Shanxi Rift from south to north. Key Points: A high‐resolution crustal and uppermost mantle shear velocity model of the Shanxi Rift is presented Thick sedimentary layers in the Datong Basin are associated with asthenospheric upwelling beneath the Datong Volcanoes High temperatures weaken the crust of the Datong Basin, leading to the shallowing of focuses of earthquakes in the northern Shanxi Rift